2022
DOI: 10.1002/joc.7835
|View full text |Cite
|
Sign up to set email alerts
|

Storm types in Bangladesh: duration, intensity and area of intra‐daily wet events

Abstract: We explore the characteristics of 96190 wet events (WE) defined as consecutive 3-hourly rainfall >= 1 mm/3h from a network of 34 stations across Bangladesh. Nearly 60% (5%) of wet events last <= 3 (>= 15) hours. The WEs are dynamically clustered into four "canonical" storm types (ST), mostly discretized by their duration, but also their mean and maximal intensity. While durations, total amounts and wet contiguous areas of WEs are positively related, their mean intensity is nearly independent of them. ~ 60% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…There is a clear relationship between the size, duration and mean rainfall intensity of the rain cells, contrary to studies focused on storm properties at a given site, which found that mean intensity is uncorrelated to storm duration (Mengouna et al, 2024, personal communication; Moron, Acharya, & Hassan, 2023). The mean lifetime (5.6 h) agrees with the figures obtained for Central Africa MCSs (Nguyen & Duvel, 2008).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…There is a clear relationship between the size, duration and mean rainfall intensity of the rain cells, contrary to studies focused on storm properties at a given site, which found that mean intensity is uncorrelated to storm duration (Mengouna et al, 2024, personal communication; Moron, Acharya, & Hassan, 2023). The mean lifetime (5.6 h) agrees with the figures obtained for Central Africa MCSs (Nguyen & Duvel, 2008).…”
Section: Discussionmentioning
confidence: 77%
“…This is in broad agreement with Lochbihler et al (2017), for the Netherlands, and with Liu (2011) and Fu et al (2020), for the tropics as a whole, who found that the mean rain rate of rain cells generally increases with the increase of their area and duration. Different results have been obtained based on station observations in Bangladesh (Moron, Acharya, & Hassan, 2023) and Central Africa (Mengouna et al, 2024, personal communication), where the duration of storm events at a given site is uncorrelated to mean hourly intensities. This is not contradictory with the present study which considers rain cells along their entire lifetime, not point rainfall.…”
Section: Resultsmentioning
confidence: 94%
“…blue line in Fig. 2 b) was observed due to rainfall dilution 34 (see Supplementary Fig. S.2 A) during the monsoon July 2013 to Sep 2013 and re-concentration through evaporation loss over the dry season Oct 2013 to March 2014 (blue line in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The 2014 evaporation and rainfall data were repeated to enable multi-year simulations. Climate change, resulting in warmer seas, is likely to result in an increase in the occurrence of severe tropical cyclones in the Bay of Bengal 25 , 34 .…”
Section: Methodsmentioning
confidence: 99%